2019
DOI: 10.1152/ajpendo.00215.2018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatic HSP72 on insulin signaling

Abstract: Heat shock protein 72 (HSP72) is a major inducible molecule in the heat shock response that enhances intracellular stress tolerance. Decreased expression of HSP72 is observed in type 2 diabetes, which may contribute to the development of insulin resistance and chronic inflammation. We used HSP72 knockout (HSP72-KO) mice to investigate the impact of HSP72 on glucose metabolism and endoplasmic reticulum (ER) stress, particularly in the liver. Under a high-fat diet (HFD) condition, HSP72-KO mice showed glucose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…Furthermore, silencing of HSP72 was shown to increase JNK activity while silencing of JNK decreased TNF-α, IL-6 and IL-8 levels, and apoptosis, while elevating cell viability. Reports have suggested that the knockout of HSP72, a natural inhibitor of JNK leads to an increase in JNK activity (Park et al 2001 ; Kitano et al 2019 ) while patients with severe COPD have been noted to exhibit upregulated levels of JNK in their adipose tissues (Tkacova et al 2011 ). Consistently, patients with COPD displayed increased numbers of positive cells for phosphorylated JNK in epithelial cells (Eurlings et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, silencing of HSP72 was shown to increase JNK activity while silencing of JNK decreased TNF-α, IL-6 and IL-8 levels, and apoptosis, while elevating cell viability. Reports have suggested that the knockout of HSP72, a natural inhibitor of JNK leads to an increase in JNK activity (Park et al 2001 ; Kitano et al 2019 ) while patients with severe COPD have been noted to exhibit upregulated levels of JNK in their adipose tissues (Tkacova et al 2011 ). Consistently, patients with COPD displayed increased numbers of positive cells for phosphorylated JNK in epithelial cells (Eurlings et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HSP72 reportedly inhibits the production of lipopolysaccharide (LPS)-induced inflammatory cytokines resulting in a decrease in inflammatory injury in murine immune cells (Muralidharan et al 2014 ). Moreover, COPD patients have been observed exhibit both upregulated activity and phosphorylation of c-Jun N-terminal kinase (JNK) (Eurlings et al 2017 ); knockdown of HSP72 has been reported to elevate the activity and phosphorylation of JNK (Kitano et al 2019 ), which may represent a potential mechanism by which HSP72 protects against inflammatory injury in the lung. However, the exact mechanism by which baicalin exerts its protective role against COPD is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have clearly shown that insulin sensitivity could be improved by HSP72 induction via heat treatment (42°C for 30 min), pharmacologic intervention, and transgenic overexpression [23,38,39]. On the other hand, mice with HSP72 deletion were prone to be obese and glucose intolerant [40], further supporting the role of HSP72 in metabolic regulation.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous reports suggest that HSP72 induction by geranylgeranylacetone (GGA) or heat shock (HS) + mild electrical stimulation (MES) attenuates metabolic abnormalities such as glucose intolerance, insulin resistance, chronic inflammation, enhanced hepatic gluconeogenesis, and steatosis in mouse models of diabetes as well as in patients with metabolic syndrome and type 2 diabetes ( 6 , 7 , 8 ). The introduction of HSP72 specifically in the liver of whole-body HSP72 knockout mice by lentivirus resulted in the amelioration of whole-body glucose homeostasis and inflammation as well as hepatic gluconeogenesis and steatosis ( 9 ). Therefore, the hepatic role of HSP72 should be more precisely investigated.…”
Section: Introductionmentioning
confidence: 99%